Proficiency-based progression training in robot-assisted laparoscopy for endometrial cancer: peri-operative and survival outcomes from an observational cohort study - Sickinghe, Ariane; Nobbenhuis, Marielle; Nelissen, Ellen; Heath, Owen; Ind, Thomas (Frontiers in Medicine, 2024)
Introduction: Over the last decade there has been a transition from traditional laparoscopy to robotic surgery for the treatment of endometrial cancer. A number of gynaecological oncology surgical fellowship programmes have adopted robot-assisted laparoscopy, but the effect of training on complications and survival has not been evaluated. Our aim was to assess the impact of a proficiency-based progression training curriculum in robot-assisted laparoscopy on peri-operative and survival outcomes for endometrial cancer. Methods: This is an observational cohort study performed in a tertiary referral and subspecialty training centre. Women with primary endometrial cancer treated with robotassisted laparoscopic surgery between 2015 and 2022 were included. Surgery would normally include a hysterectomy and salpingo-oophorectomy with some form of pelvic lymph node dissection (sentinel lymph nodes or lymphadenectomy). Training was provided according to a training curriculum which involves step-wise progression of the trainee based on proficiency to perform a certain surgical technique. Training cases were identified preoperatively by consultant surgeons based on clinical factors. Case complexity matched the experience of the trainee. Main outcome measures were intra-and post-operative complications, blood transfusions, readmissions < 30 days, return to theatre rates and 5-year disease-free and disease-specific survival for training versus non-training cases. Mann-Witney U, Pearson's chi-squared, multivariable regression, Kaplan-Meier and Cox proportional hazard analyses were performed to assess the effect of proficiency-based progression training on peri-operative and survival outcomes.Training cases had a lower BMI than non-training cases (30 versus 32 kg/m 2 , p = 0.013), but were comparable in age, performance status and comorbidities. Training had no influence on intra-and post-operative complications, blood transfusions, readmissions < 30 days, return to theatre rates and median 5-year disease-free and disease-specific survival.Operating time was longer in training cases (161 versus 137 min, p =<0.001). The range of estimated blood loss was smaller in training cases. Conversion rates, critical care unitadmissions and lymphoedema rates were comparable. Discussion: Proficiency-based progression training can be used safely to teach robot-assisted laparoscopic surgery for women with endometrial cancer. Prospective trails are needed to further investigate the influence of distinct parts of robot-assisted laparoscopic surgery performed by a trainee on endometrial cancer outcomes.